PENGARUH MOTIVASI TERHADAP KINERJA KARYAWAN PT. FASTFOOD INDONESIA DI SANGATTA - Halipah; Muhammad Nawawi Dg Sibali; Agung Prasetyo (Tinta Nusantara 2018 Vol.1, 2020)
This study aims to determine the effect of motivation on employee performance at PT. Indonesian fast food in Sangatta. The measurement scale for the indicators of each variable is a Likert scale with an interval scale of 1 to 5. The analytical method used is simple linear regression. Based on the results of the regression test analysis which shows that the motivation variable is significant and has a positive effect on the performance of the employees of PT. Indonesian fast food in Sangatta. From the results of the partial test of motivation (X) has a significant effect on employee performance at PT. Fastfood Indonesia in Sangatta with the t-count value of the motivational variable of 13.004 with a significant level of 0.000 where significant <0.05 (0.000 <0.05) and t-table of 1.701 where the value of tcount> ttable (13.004> 1.701). Thus the hypothesis is proven